Penguatan Organisasi Pembelajar Pada Organisasi Wanita Peduli dan Inspiratif (Tapis) Lampung Berjaya - Puspawati, Ani Agus; C, Susana Indriyati; Hayati, Keumala; Sulistiowati, Rahayu; Suchmasasi, Yudha (Borneo Research and Education Center, 2024)
The strength and excellence of the organization will be realized with the positive character of its members. Community service activities (PKM) at the Tapis Lampung Berjaya organization of Pringsewu Regency aim to create a learning organization. The methods carried out are situation analysis, training, and evaluation. Evaluation and Reflection. Evaluation is carried out with pre and post-tests as a quantitative measurement method of changes in cognition. Reflection was carried out at the end of the activity to strengthen commitment and awareness to actively participate in realizing learning organization. The activity was carried out on April 26, 2021. As a result of this activity, the average score of participants before participating was 55.5 and rose to 73.65 after the activity. The average increase was 18.15 points. The highest pre-test score was 75, and the lowest was 15. The highest post-test score was 83, and the lowest value was 61. This service activity can have a positive impact on realizing learning organization.